The update on transcatheter arterial chemoembolization using drug-eluting beads: Optimization for best response - Jung Suk Oh; Ho Jong Chun (Society of Gastrointestinal Intervention, 2021)
Transcatheter arterial chemoembolization using drug-eluting beads (DEB-TACE) was developed to overcome the shortcomings of conventional TACE (c-TACE) and was expected the better clinical results. Based on the published studies so far, a clear pharmacokinetic superiority or survival benefit of DEB-TACE over cTACE has not been established yet and clinical effect of DEB-TACE is controversy. However, previous published studies on DEBTACE have limitations in optimizing the DEB-TACE procedure due to the lack of detailed subgroup analysis and not including the clinical data of DEB-TACE using recently and newly developed small DEB particles. Aim of this review article is to systematically analyze the published data, especially subgroup analysis, on the optimization for best response in terms of tumor response and safety profile.